2007
DOI: 10.1055/s-2007-984405
|View full text |Cite
|
Sign up to set email alerts
|

Good Pregnancy Outcome with Emergent Cerclage Placed in the Presence of Intra-Amniotic Microbial Invasion

Abstract: Cervical insufficiency with dilation can be associated with amniotic fluid microbial invasion. Cerclage placement in the presence of infection is contraindicated because it is associated with poor fetal and maternal outcome. A 30-year-old gravida 4 para 0 with cervical insufficiency had emergent cervical suture placement at 19 weeks. The patient underwent amniocentesis to screen for infection. After the screen for infection using amniotic fluid glucose and white blood cells had indicated negative results, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…In support of this view, Miller et al found that, among women receiving an examination-indicated cerclage, pregnancy was significantly more likely to be prolonged by 28 days when patients received perioperative indomethacin and antibiotics [24]. Moreover, Mvundura et al reported good pregnancy outcomes after the successful eradication of cultureproven intra-amniotic infections that were present at the time of emergency cerclage [25].…”
Section: Discussionmentioning
confidence: 99%
“…In support of this view, Miller et al found that, among women receiving an examination-indicated cerclage, pregnancy was significantly more likely to be prolonged by 28 days when patients received perioperative indomethacin and antibiotics [24]. Moreover, Mvundura et al reported good pregnancy outcomes after the successful eradication of cultureproven intra-amniotic infections that were present at the time of emergency cerclage [25].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, http://www.unboundmedicine.com/medline/?st=M&author=Mvundura%20E et al . reported a satisfactory pregnancy outcome with antibiotic therapy and documented eradication of intra‐amniotic infection at the time of emergent cerclage placement . However, further prospective studies on the efficacy of these clinical management strategies according to the results of AF analysis may be needed.…”
Section: Discussionmentioning
confidence: 99%
“…Preterm rupture of membranes, preterm labour and chorioamnionitis were ruled out. Patients were admitted receiving indomethacin to prevent contraction and decrease fetal urine output as a theoretically way to decrease intra-amniotic pressure21 22 as well as ampicillin/sulbactan 1.5 g twice a day as prophylactic antibiotic therapy 21 23…”
Section: Methodsmentioning
confidence: 99%